2016
DOI: 10.1523/eneuro.0295-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of the Inner Hair Cell Microtubule Meshwork in a Mouse Model of Auditory Neuropathy AUNA1

Abstract: Auditory neuropathy 1 (AUNA1) is a form of human deafness resulting from a point mutation in the 5′ untranslated region of the Diaphanous homolog 3 (DIAPH3) gene. Notably, the DIAPH3 mutation leads to the overexpression of the DIAPH3 protein, a formin family member involved in cytoskeleton dynamics. Through study of diap3-overexpressing transgenic (Tg) mice, we examine in further detail the anatomical, functional, and molecular mechanisms underlying AUNA1. We identify diap3 as a component of the hair cells api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…Considering the multifocal ultrastructural changes of HCs in aged TG mice, constitutive activation of Dia1 may widely affect actin remodeling pathways in HCs. Morphological defects at the cuticular plates and stereocilia in DIA3-overexpressing mice may support our results and theories 48 . Moreover, polymerized actin plays a role in the formation of membrane invagination at synapses 49 , as well as Dia1 regulated synaptic vesicle endocytosis at the presynaptic active zone 50 .…”
Section: Discussionsupporting
confidence: 90%
“…Considering the multifocal ultrastructural changes of HCs in aged TG mice, constitutive activation of Dia1 may widely affect actin remodeling pathways in HCs. Morphological defects at the cuticular plates and stereocilia in DIA3-overexpressing mice may support our results and theories 48 . Moreover, polymerized actin plays a role in the formation of membrane invagination at synapses 49 , as well as Dia1 regulated synaptic vesicle endocytosis at the presynaptic active zone 50 .…”
Section: Discussionsupporting
confidence: 90%
“…Mapt (Tau) has been extensively studied as a microtubule-associated protein that plays a role in the elongation and stabilization of microtubules. In vestibular HCs, prominent microtubules are present in the kinocilia and in association with the cuticular plate where they serve to link the plate to the lateral cell membrane ( Surel et al, 2016 ; Takumida et al, 1995 ; Vranceanu et al, 2012 ). However, immunolocalization indicated limited expression of Mapt in HCs prior to P5, suggesting a limited role in the initial development of either the kinocilia or the cuticular plate.…”
Section: Discussionmentioning
confidence: 99%
“…I530S located in the coiled‐coli domain is another DIAPH1 mutation that causes hearing loss in patients 33 . Previous studies showed that the loss of hearing caused by DIAPH1 R1204X mutant (which is constitutively active DIAPH1) or by overexpression of wild‐type DIAPH1 or DIAPH3 in mice, resulted from defects in stereociliary bundles 30,61‐63 . But whether DIAPH3 localizes in cilia and contributes to the functions in cilia is unclear.…”
Section: Discussionmentioning
confidence: 99%